Museums and archaeology (New York, NY Routledge, 2017)
"Museums and Archaeology brings together a wide, but carefully chosen, selection of literature from around the world that connects museums and archaeology. Part of the successful Leicester Readers in Museum Studies series, it provides a combination of issue- and practice-based perspectives. As such, it is a volume not only for students and researchers from a range of disciplines interested in museum, gallery and heritage studies, including public archaeology and cultural resource management (CRM), but also the wide range of professionals and volunteers in the museum and heritage sector who work with archaeological collections"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Antiquities -- Collection and preservation; Cultural property -- Protection; Archaeology -- Social aspects; Archaeology and state